Could L-Arginine Be a Feasible Treatment for Chronic Anal Fissure? - Sara Shojaei-Zarghani; Seyed Vahid Hosseini (Iranian Journal of Colorectal Research)
Anal fissure is a common benign anorectal condition characterized by a small, painful ulcer in the skin of the anal canal below the dentate line, which gradually leads to spasm of the internal sphincter muscle.